The Influence of Brand Image and Customer Perceived Value Toward Purchase Intention on Etude House Cosmetic As A Korean Product in Pontianak. - Luthfy, Maulida Luthfy B12112014 (Jurnal Manajemen Update, 2017)
The Influence of Brand Image and Customer Perceived Value Toward  Purchase Intention on Etude House Cosmetic As A Korean  Product  in  Pontianak. By : Maulida Luthfy (B12112014)Majors: Management InternationalEkonomi and Bisnis FacultyTanjungpura University, Pontianak ABSTRACTIn this globalization era, many of cosmetic entered in Indonesia including korean cosmetic, korean wave greatly affect the lifestle of women in pontianak. In this research focus on Customer Perceived Value is custumer Assessment toward the product . Brand image is the image or perception which exists in the customers’ mind. Purchase intention is the willingness of a customer to buy a product. The purpose of this reasearch was to determine the effect of brand image and customer perceived value toward purchase intention of Etude House cosmetic as a korean product in Pontianak. The sample of this research is female, 16-40 years old. The data are obtained by using questionnaire. This research uses Validity test , Reliability test, Convergent validity test, and Path Coefficient test, which total sample is 100, and smartPLS to process the data..The result of the research shows that there is a significant positive and relationship between brand image, customer perceived value and purchase intention.      H1:Brand Image has positive and sinificant effect on Customer Perceived Value (CPV), H2 : Brand Image has positive and significant effect on Purchase Intention. H3: Customer Perceived Value (CPV) has positive and significant effect on Purchase Intention.The result show that all hypotheses were accepted.Keyword : Brand Image, Customer Perceived Value, Purchase Intention